Technical report on proposed new interior design scheme of selangor tourist information centre for Tourism Selangor Sdn Bhd at Lot P7, Jalan Indah 14/12, 40000 Shah Alam, Selangor / Nelli Nizzati Zalizam - Zalizam, Nelli Nizzati (Faculty of Architecture, Planning and Surveying, 2009)
This Diploma level Interior Design final project is towards student understanding about the interior design project’s whole aspect that had been studied from the basic level until the design proposal presentation. The selected final project is a proposed new interior design scheme of Selangor tourist information centre for Tourism Selangor Sdn Bhd at Lot P7, Jalan Indah 14/12, Seksyen 14, 40000 Shah Alam, Selangor. With the outcome of a new tourist information centre for Selangor Sdn Bhd, it is hoped to make Tourism Selangor Sdn Bhd more recognizable and assist tourists and visitors. The concept and image is also applied to both interior and exterior to appeal the centre will be able to lure more tourists and visitors. There were several researches done to succeed this tourist information centre final project, amongst them are site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design and also suitable with the Tourism Selangor Sdn Bhd corporate image in terms of function and aesthetic value.